Factors Affecting Mobile Diabetes Monitoring Adoption Among Physicians: Questionnaire Study and Path Model - Okazaki, Shintaro; Castañeda, José Alberto; Sanz, Silvia; Henseler, Jörg (JMIR Publications, 2012)
BackgroundPatients with type 1 and type 2 diabetes often find it difficult to control their blood glucose level on a daily basis because of distance or physical incapacity. With the increase in Internet-enabled smartphone use, this problem can be resolved by adopting a mobile diabetes monitoring system. Most existing studies have focused on patients' usability perceptions, whereas little attention has been paid to physicians' intentions to adopt this technology. ObjectiveThe aim of the study was to evaluate the perceptions and user acceptance of mobile diabetes monitoring among Japanese physicians. MethodsA questionnaire survey of physicians was conducted in Japan. The structured questionnaire was prepared in a context of a mobile diabetes monitoring system that controls blood glucose, weight, physical activity, diet, insulin and medication, and blood pressure. Following a thorough description of mobile diabetes monitoring with a graphical image, questions were asked relating to system quality, information quality, service quality, health improvement, ubiquitous control, privacy and security concerns, perceived value, subjective norms, and intention to use mobile diabetes monitoring. The data were analyzed by partial least squares (PLS) path modeling. Results In total, 471 physicians participated from 47 prefectures across Japan, of whom 134 were specialized in internal and gastrointestinal medicine. Nine hypotheses were tested with both the total sample and the specialist subsample; results were similar for both samples in terms of statistical significance and the strength of path coefficients. We found that system quality, information quality, and service quality significantly affect overall quality. Overall quality determines the extent to which physicians perceive the value of mobile health monitoring. However, in contrast to our initial predictions, overall quality does not have a significant direct effect on the intention to use mobile diabetes monitoring. With regard to net benefits, both ubiquitous control and health improvement are significant predictors. Net benefits in turn significantly motivate physicians to use mobile health monitoring, and has a strong influence on perceived value. Perceived value and subjective norms are predictors of intention to use. In our sample, concerns over privacy and security risk have no significant effects on intention to use mobile diabetes monitoring. Among the 3 control variables, only age significantly affected intention to use mobile diabetes monitoring, whereas experience and gender were not significant predictors of intention. ConclusionsPhysicians consider perceived value and net benefits as the most important motivators to use mobile diabetes monitoring. Overall quality assessment does affect their intention to use this technology, but only indirectly through perceived value. Net benefits seem to be a strong driver in both a direct and indirect manner, implying that physicians may perceive health improvement with ubiquitous control as a true utility by enhancing cost-effective monitoring, and simultaneously recognize it as a way to create value for their clinical practices.